Evaluation of iron and zinc in grain and grain fractions of hexaploid wheat and its related species for possible utilization in wheat biofortification. Issue 2 (16th April 2015) - Kumar, Upendra; Mathpal, Priyanka; Malik, Sachin; Kumar, Naveen; Kumar, Satish; Chugh, Vishal; Sheikh, Imran; Sharma, Prachi; Singh, Tejveer; Dhaliwal, H. S.; Kumar, Sundip
Abstract : Iron (Fe) and zinc (Zn) contents in hexaploid wheat are very low and are further reduced because of the removal of micronutrient-rich bran of wheat grains during milling and processing. Therefore, hexaploid wheat, its wild species and wheat– Aegilops kotschyi substitution lines were evaluated to identify the genome(s) carrying gene(s) for high Fe and Zn concentrations in bran and endosperm fractions of grains. It is reflected from the results that Triticum monococcum (acc. W463) may serve as a promising donor for biofortification of Fe, and Aegilops speltoides (acc. 3804) may serve as a promising donor for biofortification of Zn in the endosperm of cultivated wheat. Further, among the three wheat– Ae. kotschyi substitution lines, the higher concentration of Fe and Zn in endosperm fraction was observed in BC2 F4 63-2-13-1. The work on precise transfer of useful gene(s) from 7U k chromosome of this line is in progress to reduce linkage drag.